Can Sharing Be Taxed? - Shu-Yi Oei; Diane M. Ring (Washington University Law Review, 2016)
In the past few years, we have seen the rise of a new model of production and consumption of goods and services, often referred to as the “sharing economy.” Fueled by startups such as Uber and Airbnb, sharing enables individuals to obtain rides, accommodations, and other goods and services from peers via personal computer or mobile application in exchange for payment. The rise of sharing has raised questions about how it should be regulated, including whether existing laws and regulations can and should be enforced in this new sector or whether new ones are needed. In this Article, we explore those questions in the context of taxation. We argue that, contrary to the claims of some commentators, the application of substantive tax law to sharing is mostly (though not completely) clear, because current law generally contains the concepts and categories necessary to tax sharing. However, tax enforcement and compliance may present challenges, as a result of two distinctive features of sharing. First, some sharing businesses opportunistically pick the more favorable regulatory interpretation if there is ambiguity regarding which rule applies or whether a rule applies. The existence of these ambiguities has been exacerbated by the structures of the new sharing economy and this has led to compliance and enforcement gaps. Second, the “microbusiness” nature of sharing raises unique compliance and enforcement concerns. We suggest strategies for addressing these dual challenges, including lower information reporting thresholds, safe harbors and advance rulings to simplify tax reporting, and targeted enforcement efforts.
Keywords: Tax; Tax compliance; Rideshare; Uber; Airbnb; Tax Law